2017
DOI: 10.3390/polym9080339
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Promotes the Osteogenesis of BMP-2 in an Absorbable Collagen Sponge

Abstract: (1) Background: We tested the hypothesis that hyaluronic acid (HA) can significantly promote the osteogenic potential of BMP-2/ACS (absorbable collagen sponge), an efficacious product to heal large oral bone defects, thereby allowing its use at lower dosages and, thus, reducing its side-effects due to the unphysiologically-high doses of BMP-2; (2) Methods: In a subcutaneous bone induction model in rats, we first sorted out the optimal HA-polymer size and concentration with micro CT. Thereafter, we histomorphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 51 publications
(66 reference statements)
1
33
0
Order By: Relevance
“…In vivo, application of HA for bone regeneration has been demonstrated in craniofacial bone defects in various animal models [18]. To stimulate bone formation, HA is either (1) mixed with filler materials [9,10,[19][20][21], (2) applied as a coating material [22], or (3) used as a carrier of growth factors and cells in the bone defect [23][24][25]. However, to date, only few clinical studies exist on the use of HA in reconstructive periodontal surgery [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, application of HA for bone regeneration has been demonstrated in craniofacial bone defects in various animal models [18]. To stimulate bone formation, HA is either (1) mixed with filler materials [9,10,[19][20][21], (2) applied as a coating material [22], or (3) used as a carrier of growth factors and cells in the bone defect [23][24][25]. However, to date, only few clinical studies exist on the use of HA in reconstructive periodontal surgery [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…HyA has been shown to play an important role in the healing of bone tissue 21 . Several studies have confirmed the efficacy of HyA on the soft tissues [22][23][24][25] . Studies have more recently focused on the effects of HyA on bone healing.…”
Section: Day 21 Assessmentmentioning
confidence: 89%
“…Several studies have examined HA hydrogels for their potential as carriers for BMP-2. Injectable or implantable HA hydrogels retain BMP-2 and stimulate bone formation in vivo [ 17 , 21 27 ]. Implantation of acrylated HA hydrogel with BMP-2 accelerates bone repair in calvarial defects in rats, and injectable hydrazone-crosslinked HA hydrogels with BMP-2 stimulate bone formation in rat calvaria [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycosaminoglycans (GAGs) have been shown to improve BMP-2 bioactivity, including for obtaining the intended osteogenesis effects [ 17 ]. HA, a type of GAG, comprises linear polysaccharides made up of repeating disaccharide units of amino sugars and uronic acid, and is among the most used materials for enhancing the microenvironment for BMP-induced osteogenesis.…”
Section: Introductionmentioning
confidence: 99%